Marketing Approach in the Management of Higher Education Institutions - Mihaela DIACONU; Amalia PANDELICĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The purpose of this paper is to present relevant aspects of the marketing approach of the universities’ activities in the current market conditions of higher education institutions. Universities are placed in the position to find solutions to the problems of stakeholder characteristics and to the competition on the educational market. Marketing approach of educational services involves the orientation to internal and external customer needs, adapting the educational and scientific research approach to create a brand image of the institution as a guarantee of its sustainability in a competitive market. The conclusion that emerges is that there is a rich specialized literature appeared especially after the ‘80s that presents the marketing tools that allow the construction of viable competitive strategies as components of university management performance.